PHARMACOEPIDEMIOLOGICAL STUDIES OF ADVERSE REACTIONS OF DEVELOPED DRUGS - E. J. Kolesnikova (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2022)
The article presents the results of pharmacoeconomic studies ofadverse reactions of developed drugs in Russian Federation